Предмет: Алгебра,
автор: korelskaya01
(m+2)(m-3)=
(2x-1)(3x+5)=
(4x-3y)(2x-y)=
(a-6)(a-1)=
(a-2)(a^2-4a+1)=
(m-3)(m^2-2m+4)=
Помогите пожалуйста срочно нужно:3Решите.
Ответы
Автор ответа:
0
(m+2)(m-3)=m²+2m-3m-6=m²-m-6
(2x-1)(3x+5)=6x²-3x+10x-5=6x²+5x-5
(4x-3y)(2x-y)=8x²-6xy-4xy+3y²=8x²-2xy+3y²
(a-6)(a-1)=a²-6a-a+6=a²-7a+6
(a-2)(a²-4a+1)=a³-2a²-4a²+8a+a-2=a³-6a²+9a-2
(m-3)(m²-2m+4)=m³-3m²-2m²+6m+4m-12=m³-5m²+10m-12
(2x-1)(3x+5)=6x²-3x+10x-5=6x²+5x-5
(4x-3y)(2x-y)=8x²-6xy-4xy+3y²=8x²-2xy+3y²
(a-6)(a-1)=a²-6a-a+6=a²-7a+6
(a-2)(a²-4a+1)=a³-2a²-4a²+8a+a-2=a³-6a²+9a-2
(m-3)(m²-2m+4)=m³-3m²-2m²+6m+4m-12=m³-5m²+10m-12
Похожие вопросы
Предмет: Қазақ тiлi,
автор: akbayannn
Предмет: Математика,
автор: dolgushina310317
Предмет: Математика,
автор: sssvip897
Предмет: Физика,
автор: Аноним
Предмет: Математика,
автор: CraftOfFunBro1